The C1 wedge connection in towers for wind turbine structures, tensile behaviour of a segment test. (1st May 2023) - Cheng, Lu; Yang, Fei; Winkes, Jasper Stefan; Veljkovic, Milan
Abstract: This paper shows a part of the analysis of the development of the second generation of the C1 wedge connections for use in offshore wind turbine supporting towers. The novelty of this connection is that bolt failure is avoided under static and fatigue loads. This study aims to investigate the tensile behaviour of the connection by combining the findings of experiments and finite element (FE) analysis. Two specimens subjected to uniaxial and cyclic tensile loading tested until failure are used for illustration. Advanced quasi-static FE analysis results, considering the most detailed geometry and using an explicit dynamic solver, are compared to the experimental results. The FE analysis results agree well with the experimental results. Based on the FE model, a parametric study is carried out to analyse the influence of the bolt grade, friction coefficient between contact surfaces, and preloading force level on mechanical behaviour. Failure modes, bolt force development, and the evolution of gap opening between contacted segments are analysed. Results demonstrate that the tensile fracture of the C1 wedge connection mainly appears in the lower segment. All the investigated parameters have a negligible effect on the connection's ultimate resistance and failure mode. However, the friction coefficient between contact surfaces and bolt preload level significantly affects the connection's local deformation capacity and the response of the bolt stress range. The FE simulation provides practical guidance for designing this connection without bolt failure. Highlights: The C1 wedge connection demonstrates a concentric load transfer path. Advanced FE model is established for explaining the load transfer mechanism. Stiffness is little affected by cyclic load until it exceeds critical load. Inaccurate bolt preloading can be effectively avoided during the installation. Failure modes, bolt forces, and gap opening behaviour are analysed.